Enforcing taxes on cryptocurrencies - Hjalte Fejerskov Boas; Mona Barake (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
Cryptocurrencies pose substantial challenges to tax enforcement due to their anonymous and decentralized properties, undermining conventional regulatory practices. We study the impact of an ambitious new enforcement initiative aimed at addressing these challenges: domestic third-party reporting of crypto income. We estimate tax compliance and behavioral responses to this new policy by combining unique Danish microdata from domestic crypto platforms, administrative tax records, and cross-border bank transfers. Despite the introduction of domestic third-party reporting, over 90% of crypto investors do not declare crypto income. Moreover, we identify a significant and persistent evasion response to the policy as investors shift trading activity from domestic platforms, subject to third-party reporting, to foreign platforms outside regulatory reach. Our findings underscore the limits of domestic enforcement strategies in addressing tax evasion for decentralized, borderless assets like cryptocurrencies, highlighting the need for international coordination.
Keywords: D31; H24; H26; H31; G5; 330; Cryptocurrencies; Tax compliance; Tax enforcement